The outlining techniques in academic writing of freshmen accountancy students in Philippine higher education institution - Marmita, Kristel Joy; Saclay, Rhafael; Caimoy, Marivic; Maga, Arriana Alexa; Nacionales, Joseph; Claridad, Norberto (Journal of Language and Pragmatics Studies, 2023)
Integrating outlining techniques have aided students in the process of writing their academic papers and helped them accomplish their paper effectively. Outlining as a pre-writing practice can help students enhance their writing abilities. Accounting students are renowned to work with numbers and analyze data, but little is known about their ability to write their academic papers. This study aims to determine the outlining techniques utilized by first-year accountancy students and how these help them in their academic writing, the use of qualitative research through Interpretive Phenomenological Analysis (IPA) is applied. A total of 26 responses were gathered by interviewing first-year accountancy students in a Philippine Higher Education Institution. The study's findings revealed three outlining strategies utilized by the students: (1) utilizing the three basic outlines; (2) compiling accumulated ideas; and (3) having a goal to know the content of their academic papers. The mentioned techniques, according to the data gathered, help accountancy students organize and express their ideas and thoughts better on paper. Research results have also shown that utilizing outlining techniques not just help accountancy students in their academic paper, but also their personal lives as it also contributes to their personal development as an individual. For future research, it is suggested that a correlational study between accounting students who employ outlining techniques, and those who do not when writing academic papers be conducted.